2010
DOI: 10.1515/bc.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Loss of gap junctional intercellular communication in rat lung epithelial cells exposed to carbon or silica-based nanoparticles

Abstract: The aim of this study was to investigate whether fine and ultrafine carbon black (fC and ufC), and fine and ultrafine silica (fS, ufS) particles affect gap junctional intercellular communication (GJIC) in rat lung epithelial cells. Exposure of cells to subcytotoxic doses of ufC, fS and ufS resulted in a 63%, 59% and 77% reduction of GJIC, respectively, as determined in a dye transfer assay. In contrast to ufC, fC did not significantly alter GJIC. Changes in subcellular localization of the major gap junction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…2 that could be the cause of the observed increase in migration of cells. Similarly, uptake of similarly sized MNPs has been reported to decrease intercellular gap junction communication (40). This work found that stress kinases and β-catenin levels modulate the alterations in intercellular gap junction communication.…”
Section: Discussionmentioning
confidence: 96%
“…2 that could be the cause of the observed increase in migration of cells. Similarly, uptake of similarly sized MNPs has been reported to decrease intercellular gap junction communication (40). This work found that stress kinases and β-catenin levels modulate the alterations in intercellular gap junction communication.…”
Section: Discussionmentioning
confidence: 96%
“…After the treatment with ultrafine SiO NPs, GJIC decreased by 77%, indicating the reduction in intercellular communication and signaling. [147]…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%
“…[190] After the exposure to SiO particles (14 nm), Ale-Agha et al observed changes in the subcellular localization of connexin-43 and of β-catenin, proteins for gap junctional intercellular communication, in rat lung epithelial cells (RLE). [147] Interestingly, Huang et al reported that mesoporous SiO NPs decreased ROS production in human malignant melanoma cells (A375), a skin cancer cell line, but adversely caused an increase in cancer cell proliferation. [201] While these few described studies exhibit minor evidence of genotoxicity, it is still unknown whether the oxidative stress formed was through direct or indirect mechanisms.…”
Section: Genotoxicity Of Sio Particlesmentioning
confidence: 99%
“…Cell death receptors could also be induced by nanomaterials as discussed above. CB nanoparticles induce EGFR signaling leading to disruption of gap junctional intercellular communication 4,48 , cell proliferation and apoptosis 15 . CB nanoparticles may however activate EGFR indirectly through ROS production and activation of lipid raft signaling 49 .…”
Section: Consequences Of the Interaction Of Nanomaterials With Proteinsmentioning
confidence: 99%